One University’s Experience with Foreign-trained Teachers - Flores, Belinda Bustos (Education Policy Analysis Archives, 2001)
Texas like many states is facing a teacher shortage. The author suggests that the teacher shortage should be considered in light of the diverse school population. Across states there is a need for well-prepared teachers to work with linguistically and culturally diverse school populations. Thus, areas such as bilingual education continue to be critical shortage areas. While different attempts are currently underway to increase the number of preservice bilingual educators, another way districts have addressed this issue is to employ foreign-trained teachers as paraprofessionals or as teachers. Recently, Texas passed a regulation that would allow legally residing foreign-trained teachers to become certified Texas teachers upon passing the appropriate teacher competency exams and demonstrating English proficiency. The passing of this "fast-track" regulation appears to demonstrate that the state board is thinking out of the box by tapping into a community's resources and acknowledging that immigrants can offer the community services beyond menial tasks. However, the researcher cautions that such actions may not increase the number of teachers and may not assure teacher quality. To support this notion, the researcher offers an analysis of a university's experience with the integration of legally residing foreign-trained Mexican teachers in their bilingual education teacher preparation program. The researcher posits that increasing the number of qualified teachers does require for entities to think out of the box, such as tapping into a community's natural resources; nevertheless, any plan of action should be critically examined and deliberated.